Improving Reading Comprehension Skills Through a Whole Language Approach in Fifth Grade Elementary School Students - Aisyah, Siti; Usman, Herlina; Utami, Nidya Chandra Muji (Universitas Pendidikan Ganesha, 2024)
Reading comprehension skills are not always easy and quick for every student to master. It is still found that students and school conditions do not support reading activities, so students' reading comprehension skills do not develop optimally. Thus, an approach to learning that can improve students' reading comprehension skills is needed. This research aims to analyze the Whole Language Approach in improving reading comprehension skills for fifth-grade elementary school students. The research method for this research is to adopt the Kemmis and McTaggart action research model. The subjects of this research were 30 class V students. The data collection methods for this research are observation, interviews and tests. The data collection instruments for this research used questionnaire sheets and test questions. This data analysis technique uses two techniques: qualitative data analysis and descriptive static data analysis. The research results were that students' interpretative level reading comprehension skills only reached 48% at the beginning of the pretest. When implementing the whole language approach in cycle I, there was an increase of 78%. Moreover, It increased again until in cycle III, it became 83%. It is concluded that the whole language approach is one-way teachers can use to improve reading comprehension skills at the interpretative level. The implication of this research is that applying the Whole Language Approach can help students learn.